Assessing the Level of Soil Development as a Strategy for Land Management a Case Study in West Halmahera Regency of Indonesia - Ladjinga, Erwin; Sofyan, Adnan; Ishak, Lily; Hartati, Tri Mulya; Aji, Krishna; Robo, Sarif (TECHNO: JURNAL PENELITIAN, 2024)
Signs of soil that has undergone advanced development include clearer horizons, higher fine fraction and lower coarse fraction, brighter soil color, higher levels of free Al and Fe. Soil aggregation is increasing, to a certain extent organic matter and nutrient levels are increasing as well as CaCO levels, and soluble salts. Soil development is characterized by the occurrence of horizon differentiation as a representative of the process of change in the earth's skin both physically, chemically and biologically by reactions in the soil profile there is an addition of organic and mineral materials in the form of solid, liquid or gaseous materials, the disappearance of materials above the soil, the transfer of materials from one part to another in the soil body, the transfer of the form of mineral compounds and organic matter in the soil body This research was carried out in the village of Bobaneigo Madihutu, South Jailolo District, West Halmahera Regency from June to July 2023. The method used in data collection is a free survey method, which is an observation made directly in the field by determining the research location based on land use maps, and administrative maps. The variables observed were C-Organic, N-Total, C/N Ratio, CEC, KB which are soil chemical properties. The results showed that the study of the level of soil development in several types of land use has not experienced weathering or advanced development due to the low content of nutrients.